A community driving under the influence (DUI) study of declining arrests. (21st March 2018) - Fell, James C.
Abstract: Objective: Recent news reports in 2016 indicated that across Miami–Dade County, Florida, driving under the influence (DUI) arrests have decreased substantially. The objective of this research was to determine the reasons for the decline in DUI arrests from 2009 to 2016. Are there fewer impaired drivers on the roads? Can DUI enforcement and prosecution be improved? Methods: The following methods were used in this study: (1) Analysis of existing DUI arrest and crash data; (2) conducting and analysis of a telephone survey of reported knowledge, attitudes, and behaviors concerning impaired driving; (3) conducting and analysis of roadside surveys on the roads on weekend nights in Miami–Dade County; (4) information from focus group discussions with police and prosecutors in Miami–Dade County; and (5) a comprehensive review of the best DUI prevention practices and enforcement strategies used across the country. Results: DUI arrests decreased 64% in Miami–Dade County between 2009 and 2016. This was a significantly larger decrease than has occurred in the State of Florida as a whole (34%) and in the United States (29%) over the same time period. The decline was not due to any decline in DUI behavior in the county. Conclusions: Based upon the data and information gathered in this project, the following actions were recommended for Miami–Dade County: (1) County police chiefs need to find ways to overcome law enforcement apathy toward DUI enforcement and persuade their traffic enforcement officers to be proactive rather than reactive when it comes to identifying and making impaired driving stops. (2) County police agencies should join forces to conduct more sobriety checkpoints. Checkpoints are safer for both the police and the drivers going through them and serve as a general deterrent to impaired driving. (3) An interagency DUI task force or team of 5 to 7 officers should be established within the county. These officers would be solely dedicated to DUI enforcement and paid for by each individual agency or under a grant from the state or federal government.